Informed Consent Procedures: Responsibilities of Researchers in Developing Countries - Sánchez, Soledad (Bioethics, 2001)
We describe the informed consent procedures in a research clinic in Santiago, Chile, and a qualitative study that evaluated these procedures. The recruitment process involves information, counseling and screening of volunteers, and three or four visits to the clinic. The study explored the decision-making process of women participating in contraceptive trials through 36 interviews. Women understood the research as experimentation or progress. The decision to participate was facilitated by the information provided; time to consider it and to discuss it with partners or relatives; and perceived benefits such as quality of care, non-cost provision of methods and medical care. For some women, participation was an opportunity to express altruism. The main obstacles for participation were perceived side effects or risks. The final risk-benefit balance was strongly influenced by women’s needs. Women perceived that the consent form benefited the clinic, proving that participants had made a free decision, and benefited the volunteers by warranting their right to free medical care. The most important problem detected was occasional misunderstanding of the information given on the form. We concluded that a full decision-making process enhances women’s ability to exercise their right to choose, and assures research institutions that trials are conducted without coercion and that the participants are committed to the study. Researchers have the responsibility of conducting this process.